Histidinaemia: a benign metabolic disorder. Issue 4 (April 1996) - Lam, W K; Cleary, M A; Wraith, J E; Walter, J H
Abstract : Histidinaemia is a relatively common inherited metabolic disorder with an incidence similar to phenylketonuria. This paper reports the long term outcome of patients diagnosed by newborn screening in the north west of England. Between 1966 and 1990, 108 infants were diagnosed as having histidinaemia by a regional neonatal screening programme (incidence 1:11, 083). A further five children were detected following diagnosis in a sibling. Of the 113, nine were lost to follow up. Infants diagnosed before 1981 (n = 47) were placed on a low histidine diet (225 mg/kg/d) for an average period of 21 months (SD 4.5). All patients were reviewed regularly, Griffiths developmental quotients (DQ) were assessed at 2 and 4 years, and WISC-R intelligence quotients (IQ) at 8, 12, and 18 years. IQ data were converted to standard deviation scores (IQ SDS) to account for increasing IQ norms with time. Neither DQ nor IQ correlated with plasma histidine at diagnosis or with the mean plasma histidine throughout life. Growth was normal in all patients. There was no apparent benefit from a low histidine diet in early childhood. In contrast to other studies, there was no excess of clinical symptoms. On the basis of these findings, histidinaemia is a benign metabolic disorder that does not require treatment.